2019
DOI: 10.1002/ldr.3284
|View full text |Cite
|
Sign up to set email alerts
|

Rapid change in forms of inorganic nitrogen in soil and moderate weed invasion following translocation of wet meadows to reclaimed post‐industrial land

Abstract: Anthropogenic expansion and loss of natural environments calls for the more sustainable use of resources, including land. To combine the conservation of highly valuable meadow habitat with reclamation of post‐industrial land, 1.3 ha of turf were translocated from an urban area to basins constructed near an abandoned quarry. In contrast to the usual method of choosing similar habitats as salvage sites, the selected quarry possessed different environmental properties to the meadows, challenging their acclimatisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 32 publications
(51 reference statements)
3
21
0
Order By: Relevance
“…In the vegetation plots placed in artificial basins, with the increasing nutrient availability, the stress factors decrease and the community tend to be more mature in successionally advanced phases growing in more fertile habitat. As we found (additional analysis, unpublished), the Ellenberg's indicator values for nutrients increase considerably (ANOVA results: F = 8.39, p < .01), and the available N also increases (Chmolowska et al, ), probably because of the location of the Botanical Garden in the city and visits of the inhabitants (approximately 25,000 per year). It was found that in urbanized, anthropogenic habitats neighbored by intensively cultivated fields, the fertility and nutrient availability go up (Prokof'eva & Poputnikov, ).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In the vegetation plots placed in artificial basins, with the increasing nutrient availability, the stress factors decrease and the community tend to be more mature in successionally advanced phases growing in more fertile habitat. As we found (additional analysis, unpublished), the Ellenberg's indicator values for nutrients increase considerably (ANOVA results: F = 8.39, p < .01), and the available N also increases (Chmolowska et al, ), probably because of the location of the Botanical Garden in the city and visits of the inhabitants (approximately 25,000 per year). It was found that in urbanized, anthropogenic habitats neighbored by intensively cultivated fields, the fertility and nutrient availability go up (Prokof'eva & Poputnikov, ).…”
Section: Discussionsupporting
confidence: 54%
“…In fertilized plots, rosette growth forms; species with small leaves and short lateral spread and reproduced by seed and early flowering should decrease in abundance (Lepik, Liira, & Zobel, ). These facts were proved in the experiment basins (Chmolowska et al, ; Nowak et al, ; own observations regarding rosette taxa). However, in this case, the SLA should increase, not decrease, as we found measuring their CWM.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The soils were collected to the depth of 20 cm, mixed and sieved, using mesh (2 cm). Three randomly chosen samples of each soil were passed through mesh (2 mm) and then analysed for physical and chemical properties, as specified in [ 23 ]. The properties of these soils are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Certified reference materials were used for quality assurance of available/exchangeable element concentration analysis: ISE-859, ISE-912, and ISE-995 (WEPAL). For calibration purposes, Six Cation Standard II and Seven Anion Standard II (Dionex) were used (Chmolowska et al 2019;Stefanowicz et al 2017Stefanowicz et al , 2018Stefanowicz et al , 2021.…”
Section: Chemical Analyses Of Soilsmentioning
confidence: 99%